2018
DOI: 10.1111/njb.01605
|View full text |Cite
|
Sign up to set email alerts
|

Myxomycetes of the National Nature Park Slobozhanskiy (Ukraine): biodiversity and noteworthy species

Abstract: We found 77 species of myxomycetes in the oak and pine forests of the National Nature Park Slobozhanskiy in northeastern Ukraine. Among them, Arcyria imperialis, Didymium ovoideum, Lamproderma gulielmae, Trichia subfusca, Oligonema fulvum and Physarum spectabile are new for Ukraine. In addition, a specimen, preliminary identified as Arcyria cf. bulbosa, may represent a species new to science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
1
2
0
1
Order By: Relevance
“…5E ). These results also confirmed the results of previous studies that most members of Stemonitidales and Echinosteliales seemed to prefer acidic conditions compared with species of Physarales ( Ndiritu, Spiegel & Stephenson, 2009 ; Yatsiuk Iryna, Leontyev Dmitry & Shlakhter Mykhailo, 2018 ). Snell & Keller (2003) suggested that the occurrence and abundance of certain species were significantly related to the pH of the bark, but not to the water retention.…”
Section: Discussionsupporting
confidence: 92%
“…5E ). These results also confirmed the results of previous studies that most members of Stemonitidales and Echinosteliales seemed to prefer acidic conditions compared with species of Physarales ( Ndiritu, Spiegel & Stephenson, 2009 ; Yatsiuk Iryna, Leontyev Dmitry & Shlakhter Mykhailo, 2018 ). Snell & Keller (2003) suggested that the occurrence and abundance of certain species were significantly related to the pH of the bark, but not to the water retention.…”
Section: Discussionsupporting
confidence: 92%
“…Поширення видів міксоміцетів на території України оцінювали за електронною базою даних "Міксоміцети України" (Kryvomaz, 2010) та публікаціями 2011-2019 рр., присвяченими різноманіттю цієї групи на окремих природоохоронних територіях (Leontyev et al, 2010(Leontyev et al, , 2011a(Leontyev et al, , 2013(Leontyev et al, , 2015Morozova, 2011;Akulov et al, 2016;Dudka, Leontyev, 2017;Moreno et al, 2017;Prylutskyi et al, 2017;Dudka et al, 2018;Yatsiuk et al, 2018;. Як облікову одиницю поширеності виду використовували його згадку в публікації, що характеризує флору окремої території.…”
Section: матеріали та методиunclassified
“…The taxonomic spectrum of the local community is fundamentally influenced by the methods of detection of organisms e.g. season, duration and type of route (Leontyev et al, 2013;Yatsiuk et al, 2018), the species concept used (Leontyev & Fefelov, 2012;Leontyev et al, 2014) etc. Therefore, it is important to study taxonomic spectra using large checklists that integrate the results of long-term research carried out by different authors and using different methods.…”
Section: Introductionmentioning
confidence: 99%